2014
DOI: 10.1016/j.jped.2013.05.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of preterm birth on motor development, behavior, and school performance of school‐age children: a systematic review

Abstract: premature infants are more susceptible to motor development, behavior and academic performance impairment when compared to term infants. These types of impairments, whose effects are manifested in the long term, can be prevented through early parental guidance, monitoring by specialized professionals, and interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
90
0
23

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(127 citation statements)
references
References 44 publications
2
90
0
23
Order By: Relevance
“…[1][2][3][4][5] Maintaining healthy sleep practices may be particularly important for children born preterm, as preterm birth is also associated with the deleterious outcomes listed above. 6 In addition, children born preterm are at increased risk of sleep disorders such as obstructive sleep apnea (OSA) and periodic limb movements of sleep (PLMS). 7 If preterm children are found to have short sleep duration or irregular scheduling of bed and wake times, this may have an additive effect on daytime dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Maintaining healthy sleep practices may be particularly important for children born preterm, as preterm birth is also associated with the deleterious outcomes listed above. 6 In addition, children born preterm are at increased risk of sleep disorders such as obstructive sleep apnea (OSA) and periodic limb movements of sleep (PLMS). 7 If preterm children are found to have short sleep duration or irregular scheduling of bed and wake times, this may have an additive effect on daytime dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent review, Moreira, Magalhães, and Alves (2014) observed that most studies with prematurely born children identified the following as risk factors: behavior problems, socioeconomic level, maternal education, ethics, family conflicts and maternal distress.…”
Section: Resultsmentioning
confidence: 99%
“…Espírito Santo et al (2009) used other instruments and verified that 60% of preschoolers had behavioral problems. There is a need to consider that, in addition to children being evaluated with different instruments, participants of the study of Espírito Santo et al (2009) were predominantly extremely premature, with a gestational age less than 26 weeks, and it was already proved that the lower the gestational age and weight at birth, the higher the risk for emotional and behavioral changes during development (Moreira et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…Some children were classified as having suspect or atypical persistent motor development during childhood. If there is concomitance of two types of risk factors, biological and environmental, the likelihood of premature birth increases 39 . Prenatal care can contribute to more favorable outcomes by allowing detection and timely treatment of diseases, in addition to controlling risk factors that bring complications to the health of the woman and the baby 34 .…”
Section: Discussionmentioning
confidence: 99%